抗体分離のための溶液 (2024)
To provide a solution for accurately separating IgG4 contained in a sample.SOLUTION: An equilibration liquid equilibrates a column filled with an insoluble carrier having Fc-binding protein immobilized thereto before and/or after adding an antibody sample, which can contain at least IgG4, to the column. The equilibration liquid has a composition that satisfies at least all the conditions of the following (a)-(c) formulae. Formula (a): electric conductivity [mS/cm]≤-0.81×buffer capacity value+12.5, formula (b): buffer capacity value>0, formula (c): electric conductivity [mS/cm]>0.SELECTED DRAWING: Figure 3